Powder post beetles / Muhamad Zamil A. Aziz - A. Aziz, Muhamad Zamil (2005)
Powder post beetles were one of the insects that can damage wood product. Besides that, several of beetles damage stored wood, structural timbers and other wood products. These beetles come from at least 12 insects families and vary greatly in size, wood preference, nature of damage and other habits. Powder post beetles was one of the families beetles that was the great infesting beetles of wood. The tunneling activities of larvae and subsequent emergence of adults weakens the structural strength of wood and may destroy its appearance. This damage identification is extremely important, since control measures vary according to species. Preventing powder post beetles or other beetles infestation is important, but once damaging is found, control measures are needed.